(untitled) (Value : Jurnal Manajemen dan Akuntansi, 2025)
Financial behavior arises from a responsible financial attitude in both individual and family financial management so as to improve financial well-being. This study aims to determine the effect of financial attitude on financial well-being with the mediating role of financial behavior. The object of this research is 60 employees at the main branch office of Bank Syariah Indonesia in Yogyakarta. The sampling in this study used a purposive sampling technique using several criteria. The data collection method used a questionnaire. The data analysis tool used Smart PLS 4.0 software. The results of the instrument scale test used in this study were validity and reliability tests. Testing of the hypothesis shows that financial attitude has a positive effect on financial well-being, financial attitude has a positive effect on financial behavior, financial behavior has a positive effect on financial well-being, and financial behavior mediates the positive effect of financial attitude on financial well-being.